(untitled) (UNED Research Journal, 2025)
Introduction: Ichneumonids are a group of parasitoid wasps that play a fundamental role in the biological control of other insects. Based on their reproductive strategy, they are classified as idiobionts and koinobionts. Idiobionts paralyze or kill their host immediately after oviposition, preventing further development, while koinobionts allow the host to continue growing and developing for some time, often manipulating its physiology to benefit the wasp larva. Tropical species are poorly known. Objective: To evaluate the seasonal variation of idiobiont and koinobiont parasitoids on Barro Colorado Island, Panamá. Methodology: I analyzed Hymenoptera samples collected weekly between 2014 and 2017 as part of the ForestGeo® project, managed by the Smithsonian Tropical Research Institute. My study focused on specimens of the Ichneumonidae family, which I classified by subfamilies and reproductive strategies. Results: Idiobiont parasitoids were more abundant and remained more stable over time compared to koinobionts, which dropped sharply in numbers during 2016 and 2017. In the dry season, idiobionts became more common, while koinobiont numbers stayed about the same between wet and dry seasons. Idiobionts also had more species, especially in the dry season. However, both groups started to decline in numbers and species from 2015 onward. Conclusions: Idiobionts were more common and stable over the years than koinobionts. They also had more species in every year of the study.